(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to measure the impact of automated accounting information systems in enhancing the quality of financial reports and developing financial management in private health institutions in Riyadh, applying it to the company’s financial management. This study used some statistical methods in this study to identify the impact of using information technology on the credibility of financial statements as seen by external auditors. The research sample consisted of 100 employees who were randomly selected for a specific purpose. To achieve the objectives of the study, the questionnaire was built based on its final form, and then the data was analyzed using the SPSS program. The study reached the most important results: There is a statistically significant effect of the efficiency of workers who use information technology on the objectivity of financial statements based on the participants’ responses. There is a statistically significant effect of internal control on the use of information technology and the objectivity of financial statements according to the participants’ responses. In light of the results of the study, the researcher proposes the following recommendations: The need to conduct more studies and research on information and communication technology and job performance. The necessity of integrating information and communication technology within the company has become an imperative necessity to keep pace with the technological developments and changes witnessed by the current era. And the use of information and communication technology experts to hold practical training courses.